2013
DOI: 10.1002/aic.14219
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for preparing silver/poly(siloxane‐b‐methyl methacrylate) nanocomposites with multiple properties in the DMF‐toluene mixture solvent

Abstract: A novel method for preparing silver/poly(siloxane-b-methyl methacrylate) (Ag/(PDMS-b-PMMA)) hybrid nanocomposites was proposed by using the siloxane-containing block copolymers as stabilizer. The reduction of silver nitrate (AgNO 3 ) was performed in the mixture solvent of dimethyl formamide (DMF) and toluene, which was used to dissolve doublehydrophobic copolymer, as well as served as the powerful reductant. The presence of the PMMA block in the copolymer indeed exerted as capping ligands for nanoparticles. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Polysiloxane have unique properties as the low T g (as low as −100 °C) with little or no crystalline due to flexible SiO units. What is more, the polysiloxane have a high thermal stability and mechanical flexibility . It has been reported that high electrochemical performance could be obtained by grafting PEO the flexible polysiloxane .…”
Section: Introductionmentioning
confidence: 99%
“…Polysiloxane have unique properties as the low T g (as low as −100 °C) with little or no crystalline due to flexible SiO units. What is more, the polysiloxane have a high thermal stability and mechanical flexibility . It has been reported that high electrochemical performance could be obtained by grafting PEO the flexible polysiloxane .…”
Section: Introductionmentioning
confidence: 99%
“…The initial degradation temperature of the modified compositions of PU were observed to be enhanced indicating the strong chemical bonds formed between the urethane‐epoxy‐siloxane linkages and the good dispersion of nanoparticles in the SNC. The onset decomposition temperature of SNC was similar to that of PES due to the presence of a minute quantity of SNPs . Here the presence of PDMS gives the thermal stability to the nanocomposite.…”
Section: Resultsmentioning
confidence: 99%
“…UV irradiation of the poly(St)-poly(MMA)/SN nanocomposite, whose matrix microphase structure consists of cylindrical domains of poly(MMA) with 20 nm diameter, distributed in a continuous poly(St) phase, leads to photodecomposition of poly(MMA) and the partial removal of the attached SN aggregates. In this case, the ester groups of the MMA fragments were found to participate in the reaction with the SN, even though the energy of the Ag···RO 2 C bond is rather low [79,101]. Depending on the chemical structure of poly(MMA) and the method of its preparation, other functional groups may participate in formation of the hybrid structure.…”
Section: Hybrid Systems With An Organic Polymer Matrixmentioning
confidence: 86%
“…The use of copolymers with different structures and functionality permits controlled variation of the morphology of the SN as well as the structure and properties of the hybrid composites [98][99][100]. For example, a high content of siloxane fragments in the structure of the poly(methyl methacrylate)-PDMS block copolymer (poly(methyl methacrylate) = poly(MMA)) imparts enhanced hydrophobicity and thermal stability to its derived nanocomposites but a high concentration (>7 mass %) of SN is required to impart bactericidal activity to these materials [101].…”
Section: Hybrid Systems With An Organic Polymer Matrixmentioning
confidence: 99%